Elimination of Carryover Contamination in Real-Time Reverse Transcriptase Loop-Mediated Isothermal Amplification for Rapid Detection of the SARS-CoV-2 Virus in Point-of-Care Testing - Quyen, Than Linh; Vinayaka, Aaydha Chidambara; Golabi, Mohsen; Ngoc, Huynh Van; Bang, Dang Duong; Wolff, Anders (Frontiers in Cellular and Infection Microbiology, 2022)
Loop-mediated isothermal amplification (LAMP) is being used as a robust rapid diagnostic tool to prevent the transmission of infectious diseases. However, carryover contamination of LAMP amplified products originating from previous tests has been a problem in LAMP based bio-analytical assays. In this study, we developed a Cod-Uracil-DNA-Glycosylase real-time reverse transcriptase LAMP assay (Cod-UNG-rRT-LAMP) for elimination of carryover contamination and rapid detection of SARS-CoV-2 in point of care (POC) testing. Using the Cod-UNG-rRT-LAMP assay, the SARS-CoV-2 virus could be detected as low as 2 copies/µL (8 copies/reaction) within 45 min of amplification and could eliminate 2.63±0.17 pg (equivalent to 2.296×109 copies) of contaminants per reaction. Analysis of clinical SARS-CoV-2 samples using the Cod-UNG-rRT-LAMP showed an excellent agreement with a relative accuracy of 98.2%, sensitivity of 97.1%, and specificity of 95.2% in comparison to rRT-PCR. The results obtained in this study clearly demonstrate the feasibility of the use of the Cod-UNG-rRT-LAMP assay for applications toward point of care (POC) diagnosis of SARS-CoV-2 and on-site testing of other pathogens.